The Application of Comic-Based Learning Media in Elementary School English Subject - Astuti, Adelia Widi; Lestari, Disa Evawani (Kirana Publisher (KNPub), 2024)
This study aims to analyze the effect of comic-based learning media on learning motivation and English comprehension of grade 4 students at SDS Permata Bangsa. The background of this study is the students' low interest in learning English caused by lack of motivation and less interactive learning media. This study used a descriptive qualitative approach with data collection techniques through questionnaires and observation. The research subjects consisted of 12 grade 4 students with the duration of two learning sessions of 30 minutes each. The questionnaire was distributed at the end of session 2. The questionnaire consists of 9 likert scale statements followed by open-ended questions to provide reasons for each statement. The results showed that the use of comic media significantly improved students' motivation and English language skills. Students felt more motivated and enthusiastic in learning, and felt easier to understand the lessons. The comic incorporated two grammar: Simple Past Tense and Comparative along with vocabulary that focuses on names of animals. This study concludes that comic media can be an effective and interesting learning tool to increase students' motivation and understanding in learning English. Further research on the use of comics in inclusive classrooms are also indicated.